Utilization Of Corn Starch Amylopectin (Zea mays L.) For Coating Acetylsalicylic Acid Tablets - Dalimunthe, Gabena Indrayani; Rani, Zulmai; Fauzi, Ziza Aisyia Putri; Samran, Samran; Nindya Indah Damayanti; Siti Anisa (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Aspirin or acetylsalicylic acid is a class of NSAIDs stable in dry air, in humid air aspirin will over time hydrolyze or decompose into salicylic acid and acetic acid, with the decomposition of aspirin levels that contained in the preparation will experience degradation. Acetylsalicylic acid needs to be made in the form of thin-coated or film-coated tablets. In this research, the method used was tablet coating, followed by evaluation tests of core tablets and coated tablets. The results of this study indicate that amiloCorn starch pectin can be used as a thin layer and enteric coating. The coated tablet formulation from corn starch amylopectin has evaluation test results, namely the formula 1 tablet hardness test is 4.28 kg, formula 2 is 4.94 kg, formula 3 is 4.63 kg, size uniformity test is the diameter and thickness of formula 1 is 10.93 and 3.67 mm, formula 2 is 11.33 and 3.98 mm, formula 3 was 10.95 and 3.70 mm, average weight uniformity test for formula 1 was 389.5 mg, formula 2 was 399.5 mg, formula 3 was 393 mg, disintegration time test for formula 1 in stomach medium was 13, 31 minutes, formula 2 in the stomach medium 20.25 minutes, formula 3 in the intestinal medium 2.44 minutes, dissolution test for formula 1 in 120 minutes the solubility of the active substance reached 84%, formula 2 was 82%, formula 3 was 3% and intestinal dimedium within 210 minutes. The best formula, namely formula 3, meets the requirements for coated film.